Methods Of Teaching Islamic Values Education Amid Conflict Situation: The Case Of Bangsamoro Development Agency (BDA) In Mindanao - Lantong, Abdul; Musnandar, Aries; Tuya, Mohalidin (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
Teaching Islamic values education is considered by Muslim educators as the solution to moral crisis encountered by contemporary Muslim society including the Bangsamoro in the conflict-affected area of Mindanao, Philippines.  The purpose of the present paper is to re-examine the Bangsamoro Development Agency's (BDA) methods of teaching Islamic values education among its Muslim stakeholders in Mindanao. Through the use of the qualitative method of study, like content analysis of data gathered through library research and participant observation, the researcher found out that the BDA-tasked to determine, lead and manage development projects in conflict-affected areas of Mindanao-had successfully integrated Islamic values by applying the traditional Islamic method of education such as ta'lim, tarbiyyah, and ta'dib but through the language of modern education theory, adapted to the kind of situation they are in. Instead of using Islamic terminologies as such, the BDA used such term as experiential-learning method (lecturette, workshop, reflection and demonstration, and follow-through scheme). With this, the BDA had able to play its assigned role with the acceptance of its different stakeholders including government and non-government organizations. The present Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), which is established as a product of the MILF’s struggle, may also consider BDA’s experience to institutionalize its moral governance initiative to address the perceived corruption, manipulation, and ill-governance in this government.   Keywords: Bangsamoro Development Agency, teaching methods, Islamic values, Values education, Mindanao (Philippines)